Evaluation of Phenolic Content Variability along with Antioxidant, Antimicrobial, and Cytotoxic Potential of Selected Traditional Medicinal Plants from India - Singh, Garima; Passsari, Ajit K.; Leo, Vincent V.; Mishra, Vineet K.; Subbarayan, Sarathbabu; Singh, Bhim P.; Kumar, Brijesh; Kumar, Sunil; Gupta, Vijai K.; Lalhlenmawia, Hauzel; Nachimuthu, Senthil K. (Frontiers in Plant Science, 2016)
Plants have been used since ancient times as an important source of biologically active substances. The aim of the present study was to investigate the phytochemical constituents (flavonoids and phenolics), antioxidant potential, cytotoxicity against HepG2 (human hepato carcinoma) cancer cell lines and the antimicrobial activity of the methanol extract of selected traditional medicinal plants collected from Mizoram, India. A number of phenolic compounds were detected using HPLC-DAD-ESI-TOF-MS, mainly Luteolin, Kaempferol, Myricetin, Gallic Acid, Quercetin and Rutin, some of which have been described for the first time in the selected plants. The total phenolic and flavonoid contents showed high variation ranging from 4.44 to 181.91 µg of Gallic Acid equivalent per milligram DW (GAE/mg DW) and 3.17 to 102.2 µg of Quercetin/mg, respectively. The antioxidant capacity was determined by DPPH (IC50 values ranges from 34.22 to 131.4 µg/mL), ABTS (IC50 values ranges from 24.08 to 513.4 µg/mL) and reducing power assays. Antimicrobial activity was assayed against gram positive (Staphylococcus aureus), gram negative (Escherichia coli, Pseudomonas aeruginosa) and yeast (Candida albicans) demonstrating that the methanol extracts of some plants were efficacious antimicrobial agents. Additionally, cytotoxicity was assessed on human hepato carcinoma (HepG2) cancer cell lines and found that the extracts of Albizia lebbeck, Dillenia indica and Bombax ceiba significantly decreased the cell viability at low concentrations with IC50 values of 24.03, 25.09 and 29.66 µg/mL, respectively. This is the first report of detection of phenolic compounds along with antimicrobial, antioxidant and cytotoxic potential of selected medicinal plants from India, which indicates that these plants might be valuable source for human and animal health.